The EU between Federal Union and Flexible Integration
XV, 283 p. 14 illus.
Keywords: “Putin’s barbaric war in Ukraine tests the EU as never before. Since the invasion in February 2022, we have witnessed unity among EU member states and staunch solidarity with Ukraine. It is important that this continues. But what are the options for the next steps in the EU’s future: increased federalism or flexible integration? This volume offers valuable answers and insights across a wide range of key issues from the rule of law to economic, security, industrial policies, and income inequality. The volume provides a rich source of essential knowledge on the state of the EU.” —Anders Ahnlid, Director General of National Board of Trade Sweden. Formerly Sweden’s ambassador to Finland, the EU and the OECD, and Director General for Trade in the MFA Against a backcloth of tumultuous events in Europe, the EU faces once again the fateful question of integrating in federal union or pursuing flexible integration. The sixth volume of Interdisciplinary European Studiesexplores changes to the EU’s policies, institutions and political structures to assess patterns of integration and cooperation. It brings together scholars from economics, law, and political science to provide insights into issues with a bearing on the EU’s future, including the rule of law, the European defence union, the European public prosecutor’s office, the Recovery and Resilience Facility, and European parliamentary democracy. It presents up-to-date research and offers succinct assessments of the current state of affairs, including policy recommendations for decision-makers on European and national levels. Antonina Bakardjieva Engelbrekt is Professor of European Law at the Faculty of Law of Stockholm University, Sweden. Per Ekman is researcher in Political Science at the Department of Government, Uppsala University, Sweden. Anna Michalski is Associate Professor in Political Science at the Department of Government, Uppsala University,and Chair of the Swedish Network for European Studies in Political Science. Lars Oxelheim is Professor of International Business and Finance at University of Agder, Norway, Professor Emeritus at Lund University and affiliated to the Research Institute of Industrial Economics, Sweden.